AnalisisKomparatifTingkat Kualitas Layanan dan Kepercayaan Konsumen terhadap KepuasanKonsumen (Studi Kasus Jasa Pengiriman Barang di J&T Express dan JNE di Surabaya) - Lestari, Dwi; Andayani, Sri; Nasution, Uthe (Universitas 17 Agustus 1945 Surabaya, 2020)
Abstract The reserach method used is quantitative research with comparative types. Comparative research is research that is used to compare two or more groups of a particular variable. By using a research instrument in the form of a questionnaire. This study aims to determine differences in service quality and consumer trust in consumer satisfaction at J&T Express and JNE. The population in this study are all consumer who use J&T Express and JNE shipping services. The sample in this study was that consumers in J&T Express and JNE totaled 100 people, divided into two groups, namely J&T Express 50 respondents and JNE 50 respondents.The results showed that there were differences in service quality and consumer trust in consumer satisfaction at J&T Express and JNE. On the variable service quality get positive and significant results so that there are differences. In the variable consumer trust gets positive and significant results so that there are differences. On the variable consumer satisfaction gets positive and significant results. Keywords : comparativeanalysis,service quality, J&T Express,consumer trust,JNE